Penerapan sistem pengendalian manajemen dan pengendalian internal terhadap kinerja karyawan pelayanan medis pada puskesmas di Kota Jambi - Yustien, Reni; Herawaty, Netty (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to determine the implementation of management control systems and internal controls on the performance of medical service employees at health centers in Jambi city. The data used in this study is primary data through the distribution of questionnaires to puskesmas employees who work at Jambi city health centers. The sampling technique used was purposive sampling to obtain a sample of 10 accredited health centers. The analytical method used in this research is descriptive analysis. The first study results indicate that the management control system on the performance of medical service employees at the Jambi City Health Center has been implemented effectively. Second, internal control on the performance of medical service employees at the Jambi City Health Center has been implemented effectively. Third, the performance of employees at the Jambi City Health Center has been effective. Fourth, implementing the management control system and internal control on the performance of medical service employees at the Jambi City Health Center has been carried out effectively and efficiently.